Mechanical properties and failure mechanisms of sandwich panels with ultra-lightweight three-dimensional hierarchical lattice cores. (February 2018) - Wu, Qianqian; Gao, Ying; Wei, Xingyu; Mousanezhad, Davood; Ma, Li; Vaziri, Ashkan; Xiong, Jian
Abstract: Mechanical properties and failure mechanisms of sandwich panels with "corrugated-pyramidal" hierarchical lattice cores were investigated through analytical modeling and detailed numerical simulations. This included studying the behavior of hierarchical lattice core material under compression and shearing, as well as investigating the mechanical performance of sandwich panels subjected to in-plane compression and three-point bending. Failure maps were constructed for the hierarchical lattice cores, as well as sandwich panels with hierarchical lattice cores by deriving analytical closed-form expressions for strength for all possible failure modes under each loading. 3D printed samples were manufactured and tested under out-of-plane compression in order to provide limited experimental validation of the study. Our study provides insights into the role of structural hierarchy in tuning the mechanical behavior of sandwich structures, and new opportunities for designing ultra-lightweight lattice cores with optimal performance.